2004
DOI: 10.1196/annals.1335.027
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Reproductive Technology Achievements for Optimizing Embryo Quality

Abstract: Evaluation of morphological characteristics, to date, has been the most widely accepted method for the selection of embryos with higher developmental ability and optimization of the outcome of in vitro fertilization (IVF). Improvement in clinical results has also been pursued through attempts to generate embryos of high quality or to identify more reliable selection criteria. This work evaluates the possibility of improving embryo quality and subsequent IVF outcome in situations in which creation of supernumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…2,3 FSH treatment may affect the synthesis of sperm DNA. 4,5 It was confirmed that FSH was essential for induction and maintenance of qualitatively and quantitatively normal spermatogenesis. 6,7 As FSH has a critical role in promoting spermatogenesis, various attempts have been made to increase sperm production in infertility patients by administering of FSH.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…2,3 FSH treatment may affect the synthesis of sperm DNA. 4,5 It was confirmed that FSH was essential for induction and maintenance of qualitatively and quantitatively normal spermatogenesis. 6,7 As FSH has a critical role in promoting spermatogenesis, various attempts have been made to increase sperm production in infertility patients by administering of FSH.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies had demonstrated that recombinant human FSH (rhFSH) had a positive influence on sperm DNA integrity . FSH treatment may affect the synthesis of sperm DNA . It was confirmed that FSH was essential for induction and maintenance of qualitatively and quantitatively normal spermatogenesis …”
Section: Introductionmentioning
confidence: 94%
“…12 Oocyte retrieval was carried out under general anesthesia by a vaginal ultrasonography-guided aspiration. 12 At 16 to 18 hours after insemination or microinjection, as previously described, 25,26 oocytes were assessed for 2 pro-nuclei presence. Forty-eight hours after oocyte retrieval, embryos were classified according to their morphology and then transferred into the uterus.…”
Section: Ovarian Stimulation Ivf Icsi and Embryo Developmentmentioning
confidence: 99%
“…As the fate of the embryo is largely dependent on the oocyte from which it originates, studies have been conducted to investigate a possible association between oocyte morphology and developmental potential [27]. The extent to which the follicular microenvironment affects oocyte competence and as a consequence, embryo viability has been investigated [28]. On the basis of these studies, it can be concluded that duration of COH during follicular development plays a role in the consequent embryo development.…”
Section: Discussionmentioning
confidence: 98%